Femmes et usage des gros mots en Tunisie : transgression ou renforcement de l’hétérosexisme ? - Sonya Ben Yahmed (Genre, Sexualité et Société)
The Tunisian dirty words are words with sexual and heterosexist connotation, whose use is both taboo and widespread in Tunisia. Social reprobation for the use of dirty words is exerted on women, much more than on men. Women are supposed to be the guardians of morality, and to have a distanced and modest relation to sexuality. When women use dirty words, particularly in certain spaces, they can be severely judged and even abused. In order to question the potential transgressive character of women’s use of dirty words, this article analyzes its different contexts and their effects in terms of perpetuating or undermining sexism.